Sculptures on the Jangha (wall) of the subsidiary shrine of the Someshwar Mahadev temple complex - Temples of India Project Team (Jio Institute, 2024)
This is a closer view of the north-facing jangha (wall) of the subsidiary shrine in the southeastern corner of the Someshwar Mahadev temple complex. The wall of the pancharatha (five vertical projections on each side) shrine is very ornate. The bhadra (central projection) that faces west has the depiction of Surya. The other projections have depictions of dancers, apsaras (celestial damsels), and dikpalas (deities for cardinal directions). The presence of an image of Surya holding lotuses in the upper hands, on the exterior wall indicates that the shrine must have been dedicated to Surya.